Trauma Kepala pada Anak: Klasifikasi Hingga Pemantauan jangka Panjang - Erny Erny; Okky Prasetyo; Denny Prasetyo (Universitas Wijaya Kusuma Surabaya, 2019)
Head trauma in children are frequent caused by falling, games, traffic accidents and more. Not all of head trauma continues to be brain injury. According with this, all of doctor must be able to established the diagnosis and classified head trauma to determine the optimal management and prognosis especially related with problems of brain development after head trauma. Long-term follow up should be done especially in severe and moderate head trauma to early detection any problems about development progress in this child